Care for a child with rare disease and intellectual disability and family support - Kamyk-Wawryszuk, Agnieszka (Understanding Disability: Issues, Research, Reflections, 2021)
The aim of conducted research is to analyse support which was given by the family undertaken on children with rare disease and mental disability. The research is based on quantity analysis in comparison with diagnostic survey method. 40 parents were involved in the research. The main research question of this paper is: do the parents of children with rare disease and intellectual disability receive a practical and emotional support under taking care of son/daughter from the relatives? Basing on conducted research it might be indicated, that almost half of parents have obligations related to everyday responsibilities. As well, half of parents declared that they have as much of responsibilities connected with taking care with their child as they can manage to do. Additionally respondents marked, that all of the members of the family (wife, husband, brothers and sisters of disable child) are taking everyday responsibilities. Most of parents indicated that they received both practical and emotional support from their family members on limited level.